(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
The present research was conducted to evaluate the monthly variations of macrozoobenthos of three ponds (pond 1, bottom soil is loam; pond 2, bottom soil is sandy loam; pond 3, bottom soil is silty clay loam) in relation to soil texture types of sediment. The major groups of macro-zoobenthos recorded were Chironomidae, Oligochaeta, Mollusca and Ceratopogonidae. The values of all water quality parameters such as temperature, water depth, rainfall, transparency, dissolved oxygen, pH, free CO2, NO3-N and PO4-P were found to have positive correlations in most cases, in some cases negative correlations and in few cases significant correlations. The abundance of Chironomidae was to be dominant in the pond no. 3 during the whole study period. The highest number of Oligochaeta (400 per m2) was found in pond no. 3 at depth of 150 cm and the lowest number of Oligochaeta (0 per m2) was found in pond nos. 1, 2 and 3 at both depths. The highest number of Chironomidae (1332 per m2) was found in pond no. 3 at depth of 150 cm and the lowest number of Chironomidae (444 per m2) was found in pond no. 2 at depth of 100 cm. The highest number of Ceratopogonidae (977 per m2) was found in pond no. 3 at the depth of 150 cm and the lowest number of Ceratopogonidae (178 per m2) was found in pond no. 2 at both depths. The highest number of Mollusca (1288 per m2) was found in pond no. 3 at the depth of 150 cm and the lowest number of Mollusca (222 per m2) was found in pond no. 2 at the depth of 100 cm. Satisfactory quantity of macrobenthos in the pond no. 3 at the depth of 150 cm than those of other two ponds. Between 2 depths (100 and 150 cm), the depth of 150 cm was to have highest quantity of macro-zoobenthos in all the three ponds because this depth was most favourable for macro-zoobenthos production. In pond no. 1, 2 and 3 relation of macro-benthos (no. per m2) with chemical parameters of pond bottom-soil conditions vary pond to pond which influence primary production and also influence macro-zoobenthos production (secondary production). The highest macro-zoobenthos population density was found in pond no. 3 followed by pond no. 1 and the lowest production in pond no. 2 but macro-zoobenthos production in pond no. 2 and pond no. 1 are more or less similar and macro-zoobenthos production in pond no. 3 is different and higher than those of pond nos. 1 and 2 which indicates that silty clay loam of bottom-soil is more suitable for macrozoobenthos than other soil textural classes of bottom-soil loam and sandy loam. Int. J. Agril. Res. Innov. & Tech. 7 (2): 27-35, December, 2017